2017
DOI: 10.1016/j.jtcvs.2016.12.051
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative atrial fibrillation: The role of the inflammatory response

Abstract: Objective Abnormal atrial conduction has been shown to be a substrate for postoperative atrial fibrillation (POAF). This study aimed to determine the relationship between the location of the atrial reentry responsible for POAF, and degree of atrial inflammation. Methods Normal mongrel dogs (n = 18) were divided into 3 groups: anesthesia alone (anesthesia), lateral right atriotomy (atriotomy), and lateral right atriotomy with anti-inflammatory therapy (steroid). Conduction properties of the right and left atr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 34 publications
(39 reference statements)
1
36
0
4
Order By: Relevance
“…[1][2][3] Cardiac surgery is associated with direct and indirect myocardial injuries that are potential stimuli for adverse atrial remodeling and may increase arrhythmic risk. 1,2,4,5 Thus, it is unsurprising that high rates of atrial fibrillation occur after cardiac surgery. However, there are scant contemporary data on how various surgery characteristics contribute to this risk, limiting the development of effective predictive and preventive measures.…”
mentioning
confidence: 99%
“…[1][2][3] Cardiac surgery is associated with direct and indirect myocardial injuries that are potential stimuli for adverse atrial remodeling and may increase arrhythmic risk. 1,2,4,5 Thus, it is unsurprising that high rates of atrial fibrillation occur after cardiac surgery. However, there are scant contemporary data on how various surgery characteristics contribute to this risk, limiting the development of effective predictive and preventive measures.…”
mentioning
confidence: 99%
“…Another mechanism of PoAF is the spatial inhomogeneity of the atrial conduction. It has been described that surgical manipulation raises the inhomogeneity of the atrial conduction after surgery, resulting in PoAF 7,17 . A nonuniform dispersion of the refractoriness in the atria makes some patients vulnerable to the development of PoAF 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have proven that there are multiple factors inducing PoAF after cardiac surgery. The causes of PoAF are described to be atrial inflammation, excessive production of catecholamines, autonomic nervous system dysfunction, and interstitial mobilization of fluid with resultant changes in the volume, pressure, and neurohumoral environment [7][8][9] . The spatial inhomogeneity of the atrial conduction has been shown to be one of the causes of PoAF in an animal study 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The blanking period was defined as the first 30 days after the surgery because postoperative atrial fibrillation (POAF) could occur within 30 days after the surgery and usually disappear within 30 days after the surgery. 16,17 Therefore, POAF within 30 days after the surgery was excluded from this study. All patients were discharged on warfarin.…”
Section: Follow-upmentioning
confidence: 99%
“…The blanking period was defined first 30 days after surgery because POAF occurs within 30 days after surgery and disappears within 30 days after surgery. 16,17 Therefore, POAF within 30 days after surgery was excluded from this study. If the patients had previously had POAF, recurrence of AF was detected even though sinus rhythm was maintained after the POAF terminated.…”
Section: Study Limitationsmentioning
confidence: 99%